PENGARUH BERKUMUR JUS NANAS TERHADAP AKUMULASI PLAK PADA PENGGUNA ORTODONTI CEKAT - Puspa Dila Rohmaniar; Aliefiah Salsabila Ramadhani; Ernita Sari; Raden Aditya Wisnu Wardhana (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2023)
Background: Orthodontic treatment will take longer to fail and the benefits of orthodontic treatment will be reduced. Plaque control is divided into two, mechanical plaque control and chemical plaque control. Chemical plaque control can be done by gargling with commercial mouthwash and natural ingredients such as pineapple. Pineapple fruit contains bromelain enzyme, tannin, flavonoids, steroids, fiber and water. Objective: To determine the effect of pineapple juice gargling on plaque accumulation in fixed orthodontic users. Methods: This research design is pre experimental with one group pretest posttest design. The research subjects were 30 samples. Plaque accumulation was measured using Ortho-Plaque Index with disclosing agent gel to detect the presence of plaque before and after treatment. Results: Data were analyzed using parametric hypothesis testing, namely Paired T-Test, which obtained a significance value of 0.000. Conclusion: There is a difference before and after gargling pineapple juice on plaque accumulation in users of fixed orthodontics.